A severe case of Trichophyton rubrum-caused dermatomycosis exacerbated after COVID-19 vaccination that had to be differentiated from pustular psoriasis - Yuta Norimatsu; Yurie Norimatsu (Medical Mycology Case Reports, 2022)
We present a case of deep dermatomycosis caused by Trichophyton rubrum that developed after administration of SARS-CoV-2 BNT162b2 vaccination.A 75-year-old man was vaccinated with SARS-CoV-2 on day 0 and day 23. From day 25, pustules began to appear.A skin biopsy was performed. Tissue culture revealed the presence of Trichophyton rubrum.The patient was treated with topical luliconazole and 100 mg/day oral fosravuconazole for 84 days, after which the symptoms resolved.